Pengaruh Partisipasi Anggaran dan Akuntansi Pertanggungjawaban Terhadap Kinerja Manajerial pada Dinas Pertanian dan Ketahanan Pangan Kota Palu - Akbar Akbar; Siti Zuhroh; Nur Laila (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study was to determine and analyze how much influence partially and simultaneously Organizational Commitment (X1) and Internal Control System (X2) on the Quality of Accounting Information (Y). The data used in this study is qualitative data consisting of primary data and secondary data. The data obtained were analyzed using multiple linear regression analysis. Based on the results of the simultaneous regression test (F test) Organizational Commitment and Internal Control System have an influence on the Quality of Accounting Information. By partial test (t test) only the internal control system has an influence on the quality of accounting information while Organizational Commitment has no effect on the Quality of Accounting Information.